1975
DOI: 10.1180/minmag.1975.040.309.10
|View full text |Cite
|
Sign up to set email alerts
|

Volatility of oxides from silicate melt and the origin of moldavites

Abstract: SUMMARY. The volatilities of SiO~, Na~O, and Fe~Oa x increase with increasing thermal function within the range 1600 to 2100 ~ during the melting of a sandy-silty clay. The remaining melt is to some extent enriched in Al~O3, K,O, CaO, and MgO. Chemical analyses of the sandy-silty clay, of the glasses melted from the latter, of the silicate material evaporated and newly condensed and their correlation with increasing thermal function and bulk density of glasses, as well as with the hitherto known quantitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…). Several authors (Philpotts and Pinson ; Konta and Mráz ) suggested that the changes in element ratios (e.g., Na/Fe, Ca/Fe) resulted from chemical fractionation during evaporation and condensation processes. von Engelhardt et al.…”
Section: Discussionmentioning
confidence: 99%
“…). Several authors (Philpotts and Pinson ; Konta and Mráz ) suggested that the changes in element ratios (e.g., Na/Fe, Ca/Fe) resulted from chemical fractionation during evaporation and condensation processes. von Engelhardt et al.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate amounts of the reagent powders were weighed and mixed, then introduced in a Pt 95 Au 5 crucible and heated in a muffle furnace. In order to minimise the sodium loss by volatilisation [19,20], not less than 200 g of glass was melted and the thermal cycle was defined as follows: 1200°C for 2 h, 1400°C for 2 h and then 1100°C for 24 h. The melts were then quenched and finally crushed. Glass compositions were systematically checked by electron probe microanalysis: the aimed and obtained glass compositions are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…(17) and (18)), and by replacing logK ox , logK red and log aO 2− (Eqs. (20) and (21)) by their respective expressions, B and C parameters can be written as:…”
Section: Under Oxidizing Conditionsmentioning
confidence: 99%
“…The reagents were weighted, grinded, and heated in a Pt 95 –Au 5 crucible. In order to minimize sodium loss by volatilization, 13,14 not <200 g of glass was melted once, and the thermal cycle was defined as follows: 2 h at 1200°C, 2 h at 1400°C, and then 24 h at 1100°C. Then, the crucible was removed from the furnace and quenched in air.…”
Section: Methodsmentioning
confidence: 99%